Cultural Influences on Consumer Ethnocentrism: A Multi-Country Investigation - Sharma, Piyush (International Business Press, 2011)
Prior research shows that consumer ethnocentrism relates positively with collectivism, masculinity, and uncertainty avoidance; and negatively with long-term orientation. However, there is little evidence of the generalizability of these findings across different countries and product categories. This paper uses data from four countries (China, India, UK, and USA) to investigate the influence of eight cultural orientations on consumer ethnocentrism and to assess its nomological validity and cross-cultural measurement invariance. It also explores the impact of consumer ethnocentrism on the product evaluations and behavioral intentions for a fictitious passenger car brand and the actual product ownership of twenty commonly used products.